Validation of the German basic psychological need satisfaction in sleep scale - Frytz, Patricia; Nikoleizig, Lucie; Elbe, Anne-Marie (Frontiers in Psychology, 2025)
Basic psychological need theory posits that satisfying basic psychological needs (autonomy, competence, relatedness) is connected to overall well-being and physiological health, including sleep. The reciprocal relationship between basic psychological need satisfaction and sleep quality has been investigated in different studies. However, a domain-specific questionnaire exploring basic psychological need satisfaction with a focus on sleep does not exist. Therefore, in study 1 we constructed the Basic Psychological Need Satisfaction in Sleep Scale (BPNSS-S) through confirmatory factor analysis and item selection. A total of 227 participants completed the first version of the questionnaire. In study 2, 295 participants answered the final version of the 7-item questionnaire including measurements on sleep quality, life satisfaction, vigorous exercise and basi psychological need satisfaction in exercise. The final BPNSS-S yielded good to excellent model fit, and agreement with other scales supports the assumptions of good criterion, construct, and discriminant validity. The newly developed BPNSS-S is a reliable and valid tool for assessing basic psychological need satisfaction in the sleep domain. Application of the scale will help researchers and practitioners better understand and improve sleep quality and well-being through the lens of need satisfaction. This study lays the foundation for further studies in sleep and needs research, with the potential to guide targeted approaches that enhance sleep behavior across various populations.